KOHESI DAN KOHERENSI DALAM KARANGAN NARASI SISWA KELAS VIII SMPN 6 BOJONEGORO - Zuh Rufiah (EDU-KATA, 2014)
This study was conducted to gain the descriptionof the use of cohesion and coherence in student narratives. This research uses descriptive qualitative method. The data of this study is the narrative students of grade VIII at SMP 6 Bojonegoroin Academic Year 2012/2013 which involves 36 narratives. Data collection techniques used in this study covers test and referring technique. The results of this study indicate that in writing a narrative, students used the grammatical cohesion devices (reference types, substitutions, and conjunctions: coordinating and subordinating) , lexicalcohesion devices (kind of repetition and synonymy), and coherence devices (additive connective marker, marker of series connection/parallel, repetitive connecting marker/repetition, wholistic-sections, comparison, and results-conclusion).